Jatropha curcas L. as a Plant Model for Studies on Vegetative Propagation of Native Forest Plants - Lustosa Sobrinho, Renato; Zoz, Tiago; Finato, Taciane; Oliveira, Carlos Eduardo da Silva [UNESP]; Neto, Sebastião Soares de Oliveira; Zoz, André [UNESP]; Alaraidh, Ibrahim A.; Okla, Mohammad K.; Alwasel, Yasmeen A.; Beemster, Gerrit; AbdElgawad, Hamada (MDPI, 2022)
Highlights: Jatropha curcas L. has great potential to be used as a model plant in several studies involving native forest species. The immersion in the 2,4-D solution accelerated the emission of primary roots in hardwood cuttings. Studies on vegetative propagation of native species can use Jatropha curcas L. species as a model for obtaining important information in a short time and reducing labor costs. The immersion of cuttings of native species in solutions with low concentrations of 2,4-D can favor the rooting process and vegetative propagation. Even though it is a forest native plant, there are already several studies evaluating the small genome of Jatropha curcas L., which belongs to the Euphorbiaceae family, and may be an excellent representative model for the other plants from the same family. Jatropha curcas L. plant has fast growth, precocity, and great adaptability, facilitating silvicultural studies, allowing important information to be obtained quickly, and reducing labor costs. This information justifies the use of the species as a model plant in studies involving the reproduction of native plants. This study aimed to evaluate the possibility of using Jatropha curcas L. as a model plant for studies involving native forest plants and establish possible recommendations for the vegetative propagation of the species using hardwood cuttings. The information collected can be helpful to other native forest plant species, similar to Jatropha curcas L. To this end, the effects of hardwood cutting length (10, 20, and 30 cm) and the part of the hardwood cuttings (basal, middle, and apex) were evaluated. Moreover, the influence of immersing the hardwood cuttings in solutions containing micronutrients (boron or zinc) or plant regulators (2,4-D, GA3) and a biostimulant composed of kinetin (0.09 g L−1), gibberellic acid (0.05 g L−1), and 4-indole-3-butyric acid (0.05 g L−1). The experiments were carried out in duplicates. In one duplicate, sand was used as the substrate, and rooting evaluations were made 77 days after planting. In another duplicate, a substrate composed of 50% soil, 40% poultry litter, and 10% sand was used, and the evaluations of the saplings were performed 120 days after planting. The GA3 solutions inhibited the roots’ and sprouts’ emissions, while immersion in 2,4-D solution increased the number of primary roots at 77 days after planting. The hardwood cuttings from the basal part of the branch had the best results for producing saplings.
Keywords: auxin; clone; gibberellin; plant regulators; vegetative propagation